Haematological Parameters of Workers Exposed to Printing Chemicals: A Study in Calabar, Southern Nigeria - Patience A. Akpan Enosakhare A. Asemota Deborah A. Akepu GenevieveA. Effiong (Sokoto Journal of Medical Laboratory Science)
No abstract